Exploring Social Media Engagement of a Mosquito Control Campaign: Comparing Engagement Rates per Content Type and Content Frame - Ashley McLeod-Morin; Peyton Beattie; Shelli Rampold; Ricky Telg (Journal of Applied Communications, 2020)
This study explored the social media follower engagement of a campaign with the intention to inform Florida residents about mosquito-related topics, specifically mosquito control. Engagement rates were compared between social media content type and content frames. Text graphics without characters were the most engaged content type, while the personal responsibility frame was the most engaged frame. The social media campaign examined in this study had overall low engagement rates, which could have been attributed to factors outside the scope of this study. Future recommendations for research should determine what factors most contribute to the engagement of social media content. In-depth focus groups should also be conducted to test the frames and messages used in this study. Practitioners should consider using the personal responsibility frame when communicating with the public about mosquito-related topics. Furthermore, practitioners should also apply the use of authoritative figures when designing a campaign similar to the one in this study after determining what authoritative figures effectively resonate with the intended audience.
Keywords: Social media engagement; science communication; framing; authoritative figures